Αναζήτηση Εικόνες Χάρτες Play YouTube Ειδήσεις Gmail Drive Περισσότερα »
Είσοδος
 Βιβλία Βιβλία
Hence we derive the following RULE. Divide the coefficient of the dividend by the coefficient of the divisor, and strike out the letters of the divisor from the dividend.
An Introduction to Algebra Upon the Inductive Method of Instruction - Σελίδα 81
των Warren Colburn - 1831 - 276 σελίδες
Πλήρης προβολή - Σχετικά με αυτό το βιβλίο

## A First Book in Algebra

Fletcher Durell, Elmer Ellsworth Arnold - 1919 - 325 σελίδες
...give minus. DIVISION IIY A SINGLE TERM 46. Rule. Hence in general to divide one term by another term, Divide the coefficient of the dividend by the coefficient of the divisor ; Obtain the exponent of each literal factor in the quotient by subtracting the exponent of each letter...

## Elementary Algebra with a Table of Logarithms

Julius Lederer Neufeld - 1920 - 383 σελίδες
...e Hence the rule for division of radicals, // necessary, express the radicals with a common index. Divide the coefficient of the dividend by the coefficient of the divisor for the required coefficient. Divide the surd factor of the dividend by the surd factor of the divisor...

## The Manufacture of Pulp and Paper: A Textbook of Modern Pulp and ..., Τόμος 1

...quotient is + ; if they have unlike signs, the sign of the quotient is — . To find the quotient, divide the coefficient of the dividend by the coefficient of the divisor, and the result will be the coefficient of the quotient; to this annex the literal quantities in both dividend...

## A Second Course in Algebra, Βιβλίο 2

Edward Ira Edgerton, Perry Amherst Carpenter - 1924 - 461 σελίδες
...be of the same order or reduced to the same order. (2) Indicate the division in fractional form. (3) Divide the coefficient of the dividend by the coefficient of the divisor and the radicand of the dividend by the radicand of the divisor, wherever possible, and write the quotient...

## New Elementary Algebra Embracing the First Principles of the Science

Charles Davies - 1891 - 294 σελίδες
...exponent equal to 5 minus 3. For dividing one monomial by another, then, we deduce from the above example the following rule : — Divide the coefficient of the dividend by the coefficient of the divisor, for a new coefficient. After this coefficient write all the letters of the dividend, giving to each...